Indigenous environmental justice through coproduction of mining restoration supply chains in Australia - Urzedo, Danilo; Pedrini, Simone; Hearps, C.; Dixon, Kingsley; van Leeuwen, Stephen (2022)
Mining activities often cause displacement and disruption of Indigenous socio-cultural relations to land, water, biodiversity, and sacred entities. Due to the high disturbance and degradation that occurs as a result of mining on Indigenous lands, mine restoration and closure (MR&C) must mobilize the political agency of Indigenous Australians and provide enduring benefits beyond the life-of-mine. Here, we demonstrate that Indigenous engagements with mining restoration supply chains in Australia can only succeed if institutionalized socio-environmental inequalities are recognized and dismantled. Through environmental justice lenses, we examine critical mine restoration injustices and how Indigenous Australian participation can energize environmental self-determination. We analyze emerging restoration supply chains through the native seed collection and production activities as opportunities for nurturing transformative local collaborations, Indigenous entrepreneurship, and political participation. Our analysis shows the potential for community practices to coproduce MR&C through enduring partnerships, Indigenous-led organizations, and plural knowledge systems. Indigenous Australian leadership in coordinating investments, collaborations, techniques, and business operations is critical to transforming MR&C into democratic and equitable plans and actions on Indigenous lands where mining operates. When aligned with progressive institutional changes, restoration interventions can potentially strengthen environmental self-determination for Indigenous Australian political control over the customary use and stewardship of their lands.